Consumer Behavior and Entrepreneurship : A Netnographic Study - Dutta, Akanksha; Sharma, Anupam (AMC Indian Journal of Entrepreneurship, 2019)
Nowadays, the whole world rather, the whole universe is a global village and the credit goes to globalization. Due to globalization, the internet came and consumers started buying online products. This research paper gives a framework on consumer behaviour with collaboration of entrepreneurs. This article presents an insight into the minds of consumers and entrepreneurs. This composition also identified the areas for further investigation which can be used as a stencil for entrepreneurs to understand the online behaviour of customers. The paper also endeavoured to merge from an applied perspective, two different yet connected concepts: the Netnographic approach, and end users’ tradition.